Change of formation velocity of Bi-2212 superconducting phase with annealing ambient - Öztürk, Özgür; Yıldırım, Gürcan; Aşıkuzun, Elif; Coşkunyürek, M.; Yılmazlar, M.; Kılıç, A. (Springer Science and Business Media LLC, 2013)
This exhaustive study enables the researchers to recognize the role of the annealing conditions (temperature and time) on the microstructural, mechanical, electrical and superconducting properties of the Bi-2212 superconducting material with the aid of ρ-T, X-ray diffraction, scanning electron microscopy and Vickers microhardness (Hv) measurements. For this aim, the superconducting samples are elaborated by standard solid-state reaction route at different annealing temperature and different annealing duration. The results show that the annealing temperature of 840 °C and the annealing duration of 72 h are the best for the formation velocity of Bi-2212 superconducting phase. In this study we have focused on microhardness measurements to investigate the mechanical properties. Vickers microhardness, Young’s modulus, fracture toughness and yield strength values are calculated separately for all samples. Experimental results of hardness measurements are analyzed using the some models. Finally, the Hays–Kendall model is determined as the most successful model describing the mechanical properties of our samples.
Keywords: Physics